ANALISIS SENTIMEN TWITTER VAKSIN COVID-19 MENGGUNAKAN ALGORITMA SUPPORT VECTOR MACHINE - Frizka Fitriana; admin admin (Jurnal Informasi, Perkebunan dan Sipil, 2023)
Corona virus (2019-nCoV) or commonly known as COVID-19 is a new disease outbreak officially declared a global pandemic by the World Health Organization (WHO) on March 11, 2020. The Coronavirus itself first appeared in the city of Wuhan at the end of 2019. With the Corona Virus, it causes many citizens to die, because of that and also to minimize the impact caused by the Corona Virus, one of which is by developing a vaccine. With the vaccination for all Indonesian people, it has caused a lot of controversy and caused many people to give their opinions. With limited places to express opinions, many Indonesians choose social media as a place to channel their opinions. One of the media that is widely used by the public to give opinions about something is social media twitter. Based on the explanation of the problem above, the researcher concluded to create a study that aims to analyze the community's response to vaccination into positive and negative responses. Furthermore, public opinion will also be grouped using a method that can be used to make it happen, namely by using sentiment analysis in this study using the Support Vector Machine Algorithm (SVM). The Support vector machine algorithm has performance in the accuracy section with a value of 85%, precision performance with a value of 83.60%, recall performance with a value of 84%.